Patient-reported outcomes in Takayasu's arteritis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (MASSON EDITEUR, 2017)
Patient-reported outcomes (PROs) are assessment tools coming directly from patients about their feelings, perceptions, health-related functions, and treatment effects without interpretation by health-care providers. There is a global interest for more patient-centered care'' and PROs in rheumatology. Assessment of disease impact through patient-reported outcome (PRO) measures is a key element for clinical care and clinical research in Takayasu's arteritis (TAK). Currently there are no disease-specific PRO measures to assess quality of life for patients with TAK. Impaired health-related quality of life (HRQoL), functional status, increased anxiety, and depression were shown in patients with TAK in a few studies with generic PRO instruments such as the Short Form-36. However, it is difficult to capture disease-specific effects on patients' daily life and quality of life with these generic tools. There are ongoing efforts of Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group to develop disease-specific outcome measures in TAK.
Keywords: QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; VASCULITIS; HEALTH